Educational simulator with real-time database - Tok, Zhi Sung (2019)

(untitled)
A heat exchanger is a device used to transfer heat from one medium to another. It is widely used in different fields. Air conditioning is the most common example of everyday life. Experiments on heat exchangers have been conducted by engineering students. However, the time or cost of using this equipment is high. Therefore, people are looking for multimedia software to replace this teaching equipment, especially SOLTEQ, which is the manufacturer of engineering education teaching equipment. In response to the company's needs, the purpose of this project is to create a simulator for the heat exchanger. The Unity game engine and Google Firebase are the main tools for creating this simulator. The Unity game engine is a tool for creating own 3D objects. The properties of objects created in Unity are customizable. Firebase can be imported into the Unity project to bring more functionality. Therefore, the merger of Unity and Firebase was done in this project and produced the final product - a heat exchanger simulator with realtime database.